Brexit, Birmingham, belonging and home: the experience of secondary migrant Somali families and the dirty work of boundary maintenance. Issue 2 (15th April 2020) - Allen, Chris; Ögtem-Young, Özlem
Abstract : Purpose: This study aims to investigate the impact of the Brexit referendum on feelings of belonging and home among secondary migrant Somali families in the city of Birmingham. Here, the Brexit referendum is understood through the analytical framework of the politics of belonging in that it functioned as a political mechanism that demarcated who was able to belong and who was not. Design/methodology/approach: This research was qualitatively designed, comprising 25 in-depth, semi-structured interviews that used a whole family methodological approach. In doing so, this paper considers how the referendum challenged notions of citizenship as well as community and individual identities. Findings: For the families engaged, they experienced the referendum as a mechanism that immediately conveyed notions of "otherness" and "foreign-ness" onto them, thereby creating anxiety, uncertainty and instability. This paper argues that the emotional components of belonging were also challenged to the extent that feelings of security, safety and "home" became rendered meaningless through the disempowering impact of the referendum via the removal of autonomy and choice in the bonds that exist between people and places. Originality/value: This paper generates new knowledge about the impact of the Brexit referendum. As "one-off" event, this research provides new insights into the political, social and cultural impacts of the vote. It considers a minority group that is seen to be hard to reach and thereby under-researched.